ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DAN KINERJA KARYAWAN DENGAN MENGGUNAKAN JOB SATISFACTION SURVEY (JSS) : STUDI KASUS DI DINAS PEMBERDAYAAN MASYARAKAT, PEREMPUAN DAN PERLINDUNGAN ANAK KOTA PEKALONGAN - bayu wirawan saputro (Universitas Bina Sarana Informatika, 2017)
This This study examines which factors affect employees’ job satisfaction and tests the relationship between overall job satisfaction and work performance using Job Satisfaction Survey (JSS) Spector.From the result of Job Satisfaction Survey (JJS) analysis, the overall job satisfaction score of the respondents is 101.9, which is an indication that the average responseis represent ambivalence. While the average performance rating is 4, is represent most of the respondent's performance rank is on target plus (OTP). The result of the analysis that Job satisfaction is influenced by variable of pay, promotion, Supervision, Fringe benefit, Contingent rewards, Operating conditions, Coworkers, Nature of work, dan Communication. And Work performace is influenced by job satisfaction. Keywords: Job satisfaction, Work performance, Job Satisfaction Survey (JSS)